Optimal Allocation of Distributed Generation and Distribution Static Compensator in the Radial Distribution System - Ibrahim, Khalid Elhadi Mohamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This thesis investigates the optimum allocation and capacity of the Distribution Generators (DGs) and Distribution Static Synchronous Compensator (DSTATCOM) in the radial distribution grid to attain the best reduction in the active power dissipations, voltage drop, and annual loss cost. Four various optimization algorithms are proposed in this research namely Differential Evolution (DE), Genetics Algorithms (GA), Multi-Objective Differential Evolution (MODE), and Multi-Objective Genetic Algorithm (MOGA). First, the multi-objective function is changed into a solitary one by multiplying each objective function with a weight factor. Then, GA and DE are used to attain the optimum capacity and place of the DG and DSTATCOM in the radial distribution grid. For the case of the MOGA and MODE, the multi-objective functions are directly used without applying the weighted vector approach. After the Pareto Front are obtained, the weighted vector approach is applied to select one solution. Finally, to check the performance of the methods, IEEE 33 bus bars radial distribution network with three different loading levels namely light (62.5%), nominal (100%), and heavy (125%) is used. Furthermore, the simulated results are contrasted with the previous research works to prove the effectiveness of the proposed methods. Keywords: Distributed Generation, Distribution Static Compensator, Optimal placement, Optimal sizing, Optimization, Radial distribution system.

ÖZ: Bu tez, etkin güç dağılımı, gerilim düşüşü en iyi azalma elde etmek için radyal dağıtım ızgarasında dağıtılmış jeneratörler (DGs) ve dağıtılmış statik senkron dengelenir (DSTATCOM) optimum konumu ve boyutunu inceler ve yıllık kayıp maliyeti. Dört çeşitli optimizasyon algoritmaları bu araştırma olarak bilinen diferansiyel evrimi (DE), genetik algoritmalar (GA), çok objektif diferansiyel evrimi (MODE) ve çok objektif genetik algoritması (MOGA) önerilmektedir. İlk olarak, Multi-objektif fonksiyonu bir ağırlık faktörü ile her objektif fonksiyonu çarparak bir yalnız biri olarak değiştirilir. Sonra, GA ve DE en uygun boyutu ve DG ve DSTATCOM yer radyal dağıtım ızgarasında almak için kullanılır. MOGA ve MODE için, Multi-objektif fonksiyonları doğrudan ağırlıklı vektör yaklaşımı uygulamadan kullanılır. Pareto cephesi alındıktan sonra, bir çözüm seçilmesi için ağırlıklı vektör yaklaşımı uygulanır. Son olarak, Yukarıdaki yöntemlerin performansını onaylamak için, IEEE 33 Bus barlar radyal dağıtım ağı ile üç farklı yükleme seviyeleri olarak bilinen hafif (62,5%), normal (100%), ve ağır (125%) test edilir. Ayrıca, benzetilmiş sonuçlar, önerilen yöntemlerin etkinliğini kanıtlamak için önceki araştırma çalışmaları ile kontrastlı. Anahtar Kelimeler: Dağıtılmış jeneratörler, Dağıtılmış statik senkron dengelenir, Radyal dağıtım ızgarasında, Optimizasyon, Optimum konumu ve boyutunu
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2018. Supervisor: Assoc. Prof. Dr. Reza Sirjani.
Keywords: Electrical and Electronic Engineering; Electric power systems; Electric power distribution; Distributed Generation; Distribution Static Compensator; Optimal placement; Optimal sizing; Optimization; Radial distribution system